Application of adaptive bats sonar algorithm for solving a single objective of practical business optimisation problem PROBLEM - Nafrizuan, Mat Yahya; M. Nafis, O. Z. (Kolej Universiti Islam Selangor, 2016)
An adaptive bats sonar algorithm to solve single objective optimisation problem is presented. The proposed algorithm utilised the concept of echolocation of a colony of bats to find prey. The proposed algorithm is applied to solve two practical business optimisation problems. The problems are cost optimisation of shipping refined oil and profit optimisation of selling television sets. The acquired results show that the proposed algorithm suitable to produce the appropriate optimum solution of the considered problems. The proposed algorithm can thus be an effective method for solving of single objective optimisation problems.